Pengembangan LKPD Berbasis Pembelajaran di Luar Kelas pada Materi Ekologi untuk Meningkatkan Keterampilan Berpikir Kritis - Nisan Nisan; Supeno Supeno; Iwan Wicaksono (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The purpose of this study was to develop valid, practical, and effective outdoor learning-based worksheets to improve critical thinking skills of junior high school students. This study is a type of research and development, which in its implementation uses the ADDIE stages: analysis, design, development, implementation, and evaluation. The results of the validation of the worksheets product showed an average validation result of 99 with a very valid category. This means that this outdoor learning-based worksheets is feasible to be applied in learning activities. The results of the practicality test through the learning implementation questionnaire showed an average observation result of 91.37 which shows that the outdoor learning-based worksheets is practical to be applied in learning activities. The effectiveness of the outdoor learning-based worksheets as seen based on the N-Gain value is in the high category (very effective) with an N-Gain score > 0.7. This means that the outdoor learning-based worksheets is effective in improving students' critical thinking skills.